Recurrent cardiac arrests due to severe aortic flow obstruction by aortic cannula: a fatal complication - Datt, Vishnu; Keshav, Suman; Wadhwa, Rachna; Malik, Shradha; Naqvi, Ehtesham; Aggarwal, Saket (International Surgery Journal, 2022)
In neonates and children the blood vessels are small in calibre and the correct choice of arterial and venous cannulas together with accurate placement are crucial to avoid obstructing vascular branches and misdirecting flow or impairing venous drainage. Normally in children, to establish the cardiopulmonary bypass (CPB) one arterial cannula is inserted in the ascending aorta and single stage venous cannulae, where two cannulae inserted into the superior and inferior vena cava and joined by the Y-piece are used in the most open-heart surgeries to facilitate the circulatory, respiratory support along with the temperature management. Rarely aortic cannulation can lead to aortic dissection, aortic posterior wall rupture leading to trauma to the esophagus, dislodgement of the aortic atheroma, fatal bleeding leading even to cardiac arrest. In addition, SVC and IVC syndrome can also occur due to displacement or obstruction by the venous cannulae. However, repeated episodes of the cardiac arrests in children after successful weaning from CPB, even with the use of an appropriate size aortic cannula has not been reported in the literature to date. We wished to discuss this fatal complication after weaning from CPB, due to aortic flow obstruction by the aortic cannula in a one-year-old, 5.5 kg child following successful ventricular septal defect (VSD) repair. The institutional ethical committee clearance and clinical trial registrations are not applicable for this case report publication.